The Application of Sports Mental Health Education in the Exploration of Party Construction and Ideological and Political Education in Higher Vocational Colleges - Ying Shen, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
In the new circumstances, the reform and innovative practice of ideological and political education (PE) in colleges and universities have intensified, and various unique techniques and pathways have been created. This study examines sports mental health education (MHE) in investigating party building (PB), ideology, and physical education in higher vocational institutions. Using a questionnaire, the author surveyed 43 university shooting and archery team members. The results indicate that sports MHE considerably impacts party building, ideological education, and physical education. The findings of this study are innovative and have important theoretical and practical ramifications. The future directions of this research are crucial for researchers conducting additional research.